The mysticism of sound and music : the Sufi teaching of Hazrat Inayat Khan - Inayat Khan, 1882-1927 (Shambhala, 2022)
"A modern classic of Universal Sufism that explores the mystical dimensions of music-and the musical dimensions of mysticism. Music, according to Sufi teaching, is really a small expression of the overwhelming and perfect harmony of the whole universe-and that is the secret of its amazing power to move us. The Indian Sufi master Hazrat Inayat Khan (1882-1927), the first teacher to bring the Sufi mystical tradition to the West, was an accomplished musician himself. His lucid exposition of music's divine nature has become a modern classic, beloved not only by those interested in Sufism but by musicians of all kinds. This newly reissued edition includes a foreword by Pir Zia Inayat Khan, Hazrat Inayat Khan's grandson and the current leader of the Inayati Order, the widespread Western Sufi organization that Hazrat Inayat Khan founded"--